“I don’t learn like this”: social capital and human capital during emergency remote learning at an emerging Hispanic-serving institution - Saper, Kea (Frontiers in Education, 2026)
As American universities expand online course offerings in pursuit of diversity, equity, inclusion, and belonging goals, important questions remain about how such shifts affect underrepresented students’ educational experiences. This study examines how online learning environments shape Latinx undergraduates’ sense of belonging, opportunities to build social capital, and ultimately, human capital accumulation. Drawing on interviews with 45 participants at an Emerging Hispanic-Serving Institution during the COVID-19 pandemic, findings reveal that the rapid expansion of online learning without corresponding investments in pedagogy or infrastructure eroded students’ peer networks, weakened student-faculty relationships, and isolated students academically. These missed social connections disrupted both engagement with course material and access to institutional knowledge, ultimately compromising human capital development. The study illustrates that while online learning may increase access, it often sacrifices the relational dimensions of higher education that are crucial for academic success. The study underscores the need for substantial investment in online infrastructure and pedagogy to ensure social capital opportunities in online classrooms, and calls for a reimagining of online pedagogy to center connection and inclusion, particularly for historically marginalized students in higher education.